The Mobile intranet - Managing People and Information in a Distributed Organization - Larsson, Andreas; Larsson, Tobias; Törlind, Peter (Luleå University of Technology, 2002)
As a result of the increasing globalisation of organizations, information systems must deal with issues of mobility. Longer distances between the members can lead to a knowledge gap, which means that two groups of people working in the same organization work according to completely different bases of information. Thus, there is a need for the members of an organization to communicate efficiently across geographical and departmental boundaries. The paper discusses motives, methods and experiences from the participatory design of a versatile Intranet application currently in use at the Division of Computer Aided Design, Luleå University of Technology in Sweden.